Wiek interpretacji - Vattimo, Gianni (Przestrzenie Teorii, 2013)
Gianni Vattimo, who is both a Catholic and a frequent critic of the Church, explores the surprising congruence between Christianity and hermeneutics in light of the dissolution of metaphysical truth. As in hermeneutics, Vatimo claims, interpretation is central to Christianity. Influenced by hermeneutics and borrowing largely from the Nietzschean and Heideggerian heritage, the Italian philosopher, who has been instrumental in promoting a nihilistic approach to Christianity, draws here on Nietzsche’s writings on nihilism, which is not to be understood in a purely negative sense. Vattimo suggests that nihilism not only expands the Christian message of charity, but also transforms it into its endless human potential. In “The Age of Interpretation,” the author shows that hermeneutical radicalism “reduces all reality to message,” so that the opposition between facts and norms turns out to be misguided, for both are governed by the interpretative paradigms through which someone (always a concrete, historically situated someone) makes sense of them. Vattimo rejects some of the deplorable political consequences of hermeneutics and claims that traditional hermeneutics is in collusion with various political-ideological neutralizations.